Religious terms in the Soviet totalitarian discourse about culture in 1953–1957 - Zemszał, Piotr (Instytut Języka Polskiego Polskiej Akademii Nauk, 2015)
This paper attempts a pragmatic analysis of a way in which terms related to the sphere of religion functioned in publications of the official Soviet discourse about culture during the so-called thaw. The status of those terms in the said discourse is not easy to determine precisely. Certainly, it lacks the value of stability. The common opinion that the religious lexis was completely marginalised in the so-called newspeak must raise doubts, as any generalisation of this kind. The analysed group of expressions represented an important measure in development of persuasive discourse, with their strong emotional load and deep rooting in usage (religious or, forty years after the revolution, atheistic). It was even more useful in texts concerning culture, in which the conflict between what was considered rational (socialist realism) and irrational (e.g., modernist trends) by a sender of analysed communications was revived again during the thaw. The set of religion-related terms was perfect for visualisation of those tensions.
Keywords: religious lexis; ideological discourse; culture in the USSR